Are buckminsterfullerenes molecular ball bearings? - Lhermerout, R; Diederichs, C; Sinha, S; Porfyrakis, K; Perkin, S (American Chemical Society, 2018)
Buckminsterfullerenes (C60) are near-spherical molecules, which freely rotate at room temperature in the solid state and when dissolved in solution. An intriguing question arises as to whether C60 molecules can act as “molecular ball bearings,” that is, preventing direct contact between two solid surfaces while simultaneously dissipating shear stress through fast rotation. To explore this, we performed measurements of friction across a solution of C60 in the boundary lubrication regime. High-resolution shear and normal force measurements between mica sheets separated by C60 solution were made using a surface force balance to provide single-asperity contact and sub-nanometer resolution in film thickness. We find that, even at a small volume fraction, C60 forms a solidlike amorphous boundary film sustaining a high normal load, suggesting that this system undergoes a glass transition under confinement. The C60 film gives rise to a low friction coefficient up to moderate applied loads, and we discuss the possible relevance of the ball-bearing effect at the molecular scale.